The Involvement of the Brunei Malay Community in education on the West Coast of North Borneo, 1881–1963 - Awang Jambol, DG. Junaidah; Ismail Ali; Baszley Bee Basrah Bee (Penerbit Universiti Kebangsaan Malaysia, 2023)
The colonialist-created administration in North Borneo is a reality that has altered the native people’s mindset and way of life while also providing them with much-needed exposure to the value of education. This paper attempts to explain the changes that occurred to and within the Brunei Malay community in the advent of modern education from 1881 to 1963 and how continued opportunities and exposure by colonialists have finally persuaded their minds to accept Western-style formal education. The objective of this writing is to analyse their educational involvement in colonial education through three time periods, namely the administration of the British North Borneo Company (BNBC), the Japanese Occupation, and the British Colonial Administration. This study used the methodology of historical studies by conducting analysis on primary sources such as C.O. 874/235, C.O. 874/242, NBCA 73 Native Chief’s Advisory Council Meetings, the British North Borneo Administration Report, the British North Borneo Annual Report, and interviews with five informants among the Brunei Malay community who were involved in colonial education. The study also found that the transition of Brunei’s Malay society to modern education occurred slowly compared to other ethnic groups. This happened because the colonists were selective in their efforts to provide early education opportunities to the locals, making education accessible only to aristocrats who had influence and were interested in serving the colonists. As a result, the Brunei Malay community has had trouble competing with other more educated ethnic groups, especially in maintaining their influence, role, and position after the independence of Sabah